1999
DOI: 10.1590/s0100-204x1999000300007
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação seqüencial de cloreto de mepiquat em algodoeiro

Abstract: Com o objetivo de avaliar o efeito de doses de cloreto de mepiquat aplicadas de forma parcelada, foi conduzido, em Jaboticabal, SP, um experimento com a cultivar de algodoeiro IAC 22. O delineamento experimental foi o de blocos casualizados, com 13 tratamentos e 4 repetições. O efeito do cloreto de mepiquat sobre a redução da altura das plantas foi mais evidenciado pela dose total aplicada do que pelo uso do esquema de parcelamento. A menor dose estudada (55 g/ha) foi suficiente para que as plantas, por ocasiã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
0
0
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
3
0
0
10
Order By: Relevance
“…The results are consistent with studies by Athayde and Lamas (1999) who analyzed several times and growth regulator doses, they 58 Rev. Bras.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results are consistent with studies by Athayde and Lamas (1999) who analyzed several times and growth regulator doses, they 58 Rev. Bras.…”
Section: Resultssupporting
confidence: 90%
“…Similar results were found by Ferrari et al (2008) who found no difference between the number of bolls per plant for use regulator with single dose and split and Neves et al (2011) Athayde and Lamas (1999), found no satisfactory results when using different doses, and growth regulator application times (mepiquat chloride). Through the analysis of Table 6 it was observed that the mass of 20 bolls, showed no difference when submitted in split application of growth regulator, such results corroborate the reports of Furlani Junior et al (2003) and Zanqueta et al (2004) who found no differences between the treatments with split application of plant growth regulator with control.…”
Section: Resultssupporting
confidence: 79%
“…Ao final, os tratamentos com aplicação foliar reduziram a altura das plantas em 28% (Tabela 2), confirmando os resultados obtidos por Athayde & Lamas (1999), Furlani Junior et al (2003, Laca-Buendia (1989), Lamas (2001) e Nichols et al (2003).…”
Section: Resultsunclassified
“…Athayde & Lamas (1999) e Laca-Buendia (1989) também não verificaram e f e ito d e a p l ic a ç õ e s d o p r o d u to s o b r e e s te componente da produção, enquanto que Lamas (2001) observou maior massa seca do capulho com aplicação de reguladores de crescimento. O número de maçãs por planta, número de maçãs na posição um não foram afetadas pelo tratamento de semente através de embebição com CM (Tabelas 3 e 4).…”
Section: Quadrado Médiounclassified
See 1 more Smart Citation